THE IMPACT OF GREEN REVOLUTION ON HARYANA (International Journal of Food and Nutritional Sciences, 2022)
Green revolution means: Significant improvement in agricultural production in a short period and high level of agricultural production in a long period of time. Wonderful seeds and dwarf and early maturing varieties have brought about a sudden change in Indian agriculture. The Green Revolution in Haryana has achieved great progress in agricultural productivity but at the cost of land and water degradation. Intensive agriculture during the Green Revolution period has led to a steady increase in agricultural production due to the use of high doses of fertilizers and pesticides. The adaptation of various modern farming techniques has further strengthened the role of agriculture sector in the economic development and employment generation of Haryana. Haryana has the highest cropping intensity among Indian states; And due to the advent of Green Revolution, the production and productivity of major crops increased manifold. But the adaptation to the new farming strategy has limited the state to only two crops i.e., wheat and paddy. In addition, it results in diseased soils, pest infested crops, over-exploitation of groundwater and waterlogged deserts. Present papers describe the impact of Green Revolution on Haryana